IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SKIMMING AND SCANNING TECHNIQUES AT THE TENTH GRADE OF SMA - Pritania V. V. Mokalu; Elisabeth Z. Oroh; Ignatius J. C. Tuerah (KOMPETENSI, 2021)
This research is conducted at the tenth grade students of SMA Negeri 7 Manado in the academic year of 2020-2021. It aims to find out the effectiveness of skimming-scanning techniques in improving students’ reading comprehension. The researchers choose descriptive text in this research. The researchers take one class consists of 29 students as the sample. To reach the objective of this research, the researchers employ pre-experimental design for one class consists of pre-test, treatment, and post-test. The whole procedure isconducted via online due to the pandemic era. The researchers use several formulas such as mean score formula, standard deviation formula, and t-score formula to calculate the result. The mean score of pre-test is 68.79 and the mean score of post-test is 84.48. The hypothesis of this research shows that the t-score is higher than the t-table which means that there is an improvement in students’ reading comprehension after they got the treatment. According to the results, the researchers try to draw a conclusion that the use of skimming-scanningtechniques is effective in improving students’ reading comprehension and these two techniques are proper to be applied in the learning process.